Antagonistic activity of Diplodia pinea against phytopathogenic fungi - de Oliveira, Camila Freitas; Moura, Paula Francislaine; Rech, Katlin Suellen; da Silva Paula de Oliveira, Cristiane; Hirota, Beatriz Cristina Konopatzki; de Oliveira, Maislian; da Silva, Cristiane Bezerra; de Souza, Angela Maria; de Fátima Gaspari Dias, Josiane; Miguel, Obdulio Gomes; Auer, Celso Garcia; Miguel, Marilis Dallarmi (Folia microbiologica, 2019)
The ability of Diplodia pinea to inhibit Armillaria sp., Bjerkandera adusta, Botrytis cinerea, and Rhizoctonia sp. mycelium growth was analyzed using the double-culture method. Wild-type fungal strains were incubated in a biochemical oxygen demand incubator using potato agar dextrose medium at 24 ± 2 °C for 35 days in darkness. D. pinea significantly inhibited the growth of all fungi species tested (30.75 to 98.37% inhibition) and showed moderate antagonistic activity (antagonistic index, 14.5). Chemical analysis of D. pinea culture broth extracts revealed steroids, triterpenes, and phenolic compounds. Alkaloids were qualitatively detected in the mycelium crude extract. The presence of these compounds may be related to the antagonistic activity observed. The inhibition ability of D. pinea is due to competition with the tested fungi for substrate and space.
Keywords: Culture Media; Plant Diseases; Triterpenes; Ascomycota; kyslík; nemoci rostlin; alkaloidy; triterpeny; antibióza; Mycelium; Alkaloids; kultivační média; mycelium; Oxygen; Botrytis; Antibiosis